Syndrome of inappropriate antidiuretic hormone secretion related to Guillain-Barré syndrome after laparoscopic cholecystectomy - Çakirgöz,Mensure Yilmaz (2014)
Background and objectives: Guillain-Barré Syndrome is one of the most common causes of acute polyneuropathy in adults. Recently, the occurrence of Guillain-Barré Syndrome after major and minor surgical operations has been increasingly debated. In Guillain-Barré syndrome, syndrome of inappropriate antidiuretic hormone secretion and dysautonomy are generally observed after maximal motor deficit. Case report: A 44-year-old male patient underwent a laparoscopic cholecystectomy for acute cholecystitis. After the development of a severe headache, nausea, diplopia, and attacks of hypertension in the early postoperative period, a computer tomography of the brain was normal. Laboratory tests revealed hyponatremia linked to syndrome of inappropriate antidiuretic hormone secretion, the patient's fluids were restricted, and furosemide and 3% NaCl treatment was initiated. On the second day postoperative, the patient developed numbness moving upward from the hands and feet, loss of strength, difficulty swallowing and respiratory distress. Guillain-Barré syndrome was suspected, and the patient was moved to intensive care. Cerebrospinal fluid examination showed 320 mg/dL protein, and acute motor-sensorial axonal neuropathy was identified by electromyelography. Guillain-Barré syndrome was diagnosed, and intravenous immune globulin treatment (0.4 g/kg/day, 5 days) was initiated. After 10 days in the intensive care unit, at which the respiratory, hemodynamic, neurologic and laboratory results returned to normal, the patient was transferred to the neurology service. Conclusions: Our case report indicates that although syndrome of inappropriate antidiuretic hormone secretion and autonomic dysfunction are rarely the initial characteristics of Guillain-Barré syndrome, the possibility of postoperative syndrome of inappropriate antidiuretic hormone secretion should be kept in mind. The presence of secondary hyponatremia in this type of clinical presentation may delay diagnosis.